Effect of Fe Loading Condition and Reductants on CO2 Reduction Performance with Fe/TiO2 Photocatalyst - Akira Nishimura; Noriaki Ishida; Daichi Tatematsu; Masafumi Hirota; Akira Koshio; Fumio Kokai; Eric Hu (International Journal of Photoenergy)
Fe-doped TiO2 (Fe/TiO2) film photocatalyst was prepared by sol-gel and dip-coating process and pulse arc plasma method. The effect of pulse number on the CO2 reduction performance with the Fe/TiO2 was investigated in this study. In addition, the effect of reductants such as H2O, H2, and NH3/H2O on the CO2 reduction performance with the Fe/TiO2 photocatalyst was also investigated. The characteristics of the prepared Fe/TiO2 film coated on a netlike glass fiber which is a base material were analyzed by SEM, EPMA, EDX, and EPMA. Furthermore, the CO2 reduction performance of the Fe/TiO2 film was tested under a Xe lamp with or without ultraviolet (UV) light. The results show that the CO2 reduction performance with the pulse number of 100 is the best with H2O and/or H2 as reductant under UV light illumination, while that with the pulse number of 500 is the best when NH3/H2O is used as reductant. On the other hand, the CO2 reduction performance with the pulse number of 500 is the best under every reductant condition without UV light illumination. The highest CO2 reduction performance with the Fe/TiO2 is obtained under H2 + H2O/CO2 condition, and the best moral ratio of total reductants to CO2 is 1.5 : 1.